"Transfer occurrences in the use of English prepositions (in, on, at, over, to, for, by) among eight graders at Colegio Básico General San Mateo, David, 2014" - Esquivel Saldaña, Marvin Ameth; Espinosa Vega, Katherine Dennisse (David, Panamá : UDELAS, 2014)
This thesis is focused on a researach about the transfer occurrences the students show at time to use the prepositons where the principal objetive is to prove the factors that influences in transfe occurrences in the use of english prepositions. Also, to mention some specific techniques to reduce this problem for learners.
TABLE OF CONTENTS Tables index Graphic index Introduction CHAPTER I: ANTECEDENTS OF THE PROBLEM 1.1. Antecedents 1.2. Statement of the problem 1.2.1. Formulation of the problem 1.3. Objectives 1.3.1. General Objective 1.3.2. Specifics Objectives 1.4. Justification 1.5. Scope and delimitation 1.5.1. Limitation 1.5.2. Delimitation CHAPTER II: THEORICAL FRAMEWORK 2.1. Factors that influence in the transfer occurrences 2.1.1. Mother tongue 2.1.2. Culture 2.1.3. Family 2.1.4. Teaching methodology 2.1.5. Motivation 2.2. Transfer occurrences in the use of the most common prepositions 2.2.1. Definition of transfer occurrences 2.2.1.1. Positive transfer 2.2.1.2. Negative transfer 2.2.2. Why are common the transfer occurrences in the use of english preposition 2.2.3. Grammar facts about english prepositions 2.3. Linguistic characteristics of english prepositions 2.3.1. Prepositions and morphology 2.3.2. Prepositions and syntax 2.3.3. Prepositions and lexicon 2.3.4. Prepositions and semantic 2.3.5. Use of the prepositions in, on, at, over, by, to and for 2.4. Specific techniques to reduce negative transfer of english 2.4.1. The teaching of english prepositions ti spanish native speakers 2.4.2. The role of grammar in teaching english as a second language 2.4.3. Techniques to reduce the negative transfer in the use of prepositions CHAPER III: METHODOLOGICAL ASPECTS 3.1. Type of research 3.2. Information sources 3.2.1. Human sources 3.2.2. Printed and digital sources 3.3 Variable system 3.3.1. Factors that influence 3.3.1.1. Conceptual definition 3.3.1.2. Instrumental definition 3.3.1.3. Operational definition 3.3.2. Transfer occurrences in the use of the most common prepositions 3.3.2.1. Conceptual definition 3.3.2.2. Instrumental definition 3.3.2.3. Operational definition 3.3.3. Lingustic characteristics of english prepositions 3.3.3.1. Conceptual definition 3.3.3.2. Instrumental definition 3.3.3.3. Operational definition 3.3.4. Specific techniques to reduce negative transfer of english prepositions 3.3.4.1. Conceptual definition 3.3.4.2. Instrumental definition 3.3.4.3. Operational definition 3.3.4. Strategy or methodological design for data collection and CHAPTER IV: ANALYSIS AND RESULTS 4.1. Analysis of the survey to the sustents 4.1.1. Factors that influence in the transfer occurrences Item 1 Item 2 Item 3 Item 4 4.12. Transfer occurrences in the use of the most common preposition Item 5 Item 6 4.1.3. Specific techniques to reduce negative transfer of english prepositions Item 7 4.2. Analysis and interpretation of the interview applied to the english teachers of Centro Básico San Mateo 4.2.1. Variable: Factors that influence in the transfer occurrences Item 1: The mother tongue Item 2: Motivation Item 3: Family Item 4: Culture Item 5: Teaching methodology 4.2.2. Variable: Transfer occurrences in the use of the most common prepositions Item 1: Definition of transfer occurrences Item 2: Definition of transfer occurrences Item 3: Why are common the transfer occurrences in the use of english prepositions? Item 4: Grammar facts about english prepositions 4.2.3. Variable: Linguistic characteristics of english prepositions Item 1: Prepositions and semantics Item 2: Use of the prepositions in, on, at, over, by, to adn for 4.2.4. Variable: Specific techniques to reduce negative transfer of english prepositions Item 1: The role of grammar in teaching english as a second language Item 2: Techinques to reduce the negative transfer in the use of prepositions Conclusion Bibliographical references Annexes
Incluye Table of contents
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés.
Incluye Bibliografía
No se presta a domicilio.
No se saca fotocopias.
Keywords: ENGLISH -- TESIS; INGLÉS -- TESIS; GRAMMAR -- ENGLISH -- TESIS; LICENCIATURA EN DOCENCIA EN INGLÉS - TESIS; COLEGIO BÁSICO GENERAL SAN MATEO; ENGLISH PREPOSITIONS